Effect of pH, heat treatment and enzymes on the antifungal activity of lactic acid bacteria against Candida species - Bulgasem B.Y.; Hassan Z.; Huda-Faujan N.; Omar R.H.A.; Lani M.N.; Alshelmani M.I. (Universiti Sains Malaysia, 2024)
Aims: The objectives of this study were to evaluate the inhibitory activity of the cell-free supernatants (CFS) of lactic acid bacteria (LAB) isolates and determine the effect of pH, enzymes and heat treatment on the antifungal activity against Candida species. Methodology and results: A total of 25 strains of LAB were isolated from honey samples from Malaysia, Libya, Saudi Arabia, and Yemen. Four from twenty-five LAB isolates showed antifungal activity against Candida spp. and were identified as Lactobacillus plantarum (HS), L. curvatus (HH), Pediococcus acid lactic (HC), and P. pentosaceus (HM) using 16S rDNA sequence. The CFS of these isolates were evaluated for their antifungal activity using microtiter plate assay. The antifungal activity showed significant inhibitory activity against all Candida spp. especially growth of C. glabrata ATCC 2001 was significant (p < 0.001) completely inhibited by CFS of HH and HM at pH 3. Similarly, growth of C. glabrata ATCC2001 was significantly inhibited (p < 0.001) when treated with previously heated CFS of L. curvatus HH and P. pentosaceus HM at 90 C and 121 C. While, the growth of C. krusei ATCC 6258 was completely inhibited by CFS of L. curvatus HH at 121 C. Treatment the CFS of LAB isolates with proteinase K and RNase II increased the antifungal activity against C. krusei and C. glabrata, whereas the activity of CFS produced by P. acidilactici was lost when treated with RNase II, especially against C. krusei. Conclusion, significance and impact of study: This study demonstrated that treated supernatant of LAB isolates with heating, adjusted pH and enzymes can be used to inhibit the growth of pathogenic Candida spp.